Strategi Pemasaran Digital dan Inovasi Produk dalam Meningkatkan Daya Saing Kuliner Tradisional: Studi Kasus Tape Singkong Bapak Yaya di Kota Bandung - Alamsyah, Saeful Hadi; Humaeriyah, Hani (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze digital marketing strategies and product innovation in increasing the competitiveness of traditional culinary, with a focus on the study of Mr. Yaya's Cassava Tape business in Bandung City. As a cultural heritage product, cassava tape faces significant challenges in maintaining relevance amidst the tight competition of the modern culinary industry and changes in consumer behavior. The method used in this study is descriptive qualitative with a business feasibility study approach that includes aspects of marketing, consumer behavior, and marketing mix analysis. Data were collected through direct observation, interviews, and distributing questionnaires to customer respondents to map market preferences. The results of the study indicate that although Mr. Yaya's Cassava Tape has quite good customer loyalty, optimization of digital marketing aspects through social media and brand identity updates are very necessary to expand market reach. Furthermore, innovation in packaging and diversification of flavors are key factors in increasing product appeal to the younger generation. This research emphasizes the importance of technology integration in a more structured marketing and financial management system to maintain business sustainability in the era of global competition.